THE VARIATION OF A WHEAT QUALITY INDEX IN RELATION TO MINERAL FERTILIZATION; CASE STUDY ON STARCH - Alina Laura AGAPIE; Florin SALA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study evaluated the variation of starch content (ST) in wheat grains, under the influence of mineral fertilization. The experimental were organized and carried out in the period 2020 - 2021, within the SCDA Lovrin, Romania. The Ciprian wheat variety was cultivated by appropriate culture technology, in non-irrigated system, on a chernozem type soil. Three doses for nitrogen was applied (0, 60 and 120 kg ha-1), two doses for phosphorus (0 and 60 kg ha-1), and four doses for potassium (0, 40, 80 and 120 kg ha-1). The starch content (ST, %) was determined by the non-destructive method (NIR), PERTEN INFRAMATIC 9200 device. Values of the starch content were recorded between 68.60–72.17±0.30% in the conditions of 2020 year, 69.15–72.73±0.26% in the conditions of 2021 year, respectively 68.94–72.42±0.28% as average values, over the study period. The data series distribution, average values over study period, was as a normal type, and safety vas confirmed by correlation coefficient (values between r=0.829 in the case of V15, and r=0.985 in the case of V10). ST variation, depending to N and PK (as a direct and interaction effect of fertilizers), was evaluated by regression analysis (R2=0.880, p<0.001). Based on the values of the coefficients of the obtained equation, the optimal values for N and PK were calculated and the values xopt=75.10 kg N ha-1 active substance (a.s.), and yopt=120.00 kg PK ha-1 a.s. were obtained. The Cluster analysis used, facilitated the grouping of the tested variants, based on the Euclidean distances, in relation to the starch content values recorded in the wheat grains.